Words that Compel, Emotions that Sell: Register Variation and Persuasive Strategies in English Advertising Media - Santika Agustini, Wawang (International Journal of English Language and Pedagogy, 2025)
This is research on registers used in English advertisements. Register is the term used for a variety of languages determined by subject matter. It is identified by certain phonological variants, vocabulary, or grammar that are associated with different occupational groups or subject matter. The objective of this research is to describe the specific words, the forms, and the functions of the registers. The specific words are the words that are most often used in English advertisements; the forms are the structures of the specific words; the functions are the utilities of the specific words. The advertisements that the researcher takes are: 1. Apartment, house, and hotel 2. Beverage and food 3. Cafe, restaurant, and food 4. Cosmetic 5. Vacancy. This research is descriptive qualitative because it is presented qualitatively. There is neither numeral nor counting data in this research. The sources of data are television, magazines, and newspapers. The researcher used a noting technique in collecting the data. To analyse the data, she used transferring, separating, and changing techniques. The result of the research reveals that every kind of advertisement has its own specific words, which are its registers. These specific words frequently appear in certain advertisements so that people can easily guess what kind of advertisement those weights belong to. These specific words have some forms: one-word form (noun, adjective, verb, adverb, and preposition), phrase forms (noun phrase and adjective phrase), phrasal verb form, and idiom form.